Uji Waktu Pengerasan Gipsum sebagai eksperimen Skills Lab di Universitas Trisakti - Margaretta, Dewi Liliany; Eddy, Eddy; Pratiwi, Deviyanti; tjandrawinata, rosalina; Octarina, Octarina; Kurniawan, Florencia Livia; Putri, Tansza Setiana (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2022)
Gypsum is a material that is commonly used in dentistry as study model or working model. The accuracy of the working model is influenced by the absence of defects in the model. Dental students need to know the gypsum setting time in order to avoid fracture of the model when opening the model from negative impression before reaching final setting time. Gypsum setting time can be affected by several factors such as water temperature, water ratio, room temperature and mixing speed. Measurement of gypsum setting time has been done before, however, the number of samples used was still few. Therefore, the aim of this study was to determine the setting time of gypsum with different water/powder ratio on a big number of samples. This research was done by dental students of Faculty of Dentistry, Universitas Trisakti as one of Dental Material’s Courses. A total of three types of water ratios were used in this study, namely 27 cc, 30 cc and 33 cc (n = 141). Type III gypsum powder was weighed with the same weight of 100 gr and then mixed by different water ratios for 60 seconds. Gypsum mixture was placed on a container and vibrated for 60 seconds to eliminate pores. The placement of a small needle to measure the setting time begins at the 150th second and was repeated in multiples of 30 seconds until the tip of the needle did not penetrate the gypsum mixture. The results showed that more water ratio caused the setting time of gypsum type III increased.